Developing Environmental Building Assessment Systems in Egypt The Proposal of Green Pyramid Rating System for Existing Buildings - Dr. Mohamed Saad Attwa, Dr. Magdy Qassem, Haitham Emad El-Din Morsy, (Design Engineering, 2021)
In recent times construction technology has experienced several breakthroughs in the development of building materials. These developments underscore the call for sustainable construction. The sustainability of the building is required because of avoiding the negative impacts that are happening today on the environmental system and the failure to achieve the sustainability of these buildings. At the local level (Egypt); the country is taking serious steps to guide the construction industry towards a more sustainable path. At the same time, we find many research studies that indicated that the system adopted in Egypt to classify sustainable buildings (the green pyramid system) needs to be developed to be more effective and usable. We in Egypt suffer from the lack of a system capable of evaluating existing buildings in a way that allows those Buildings have to play the role assigned to them. This role depends on preserving the environment. From here, it becomes clear to us the need to take advantage of the globally applicable regulations to access this system so that existing standards are modified and additional standards are developed that are more adaptive and appropriate to local conditions. Accordingly, this paper proposes a system for evaluating the sustainability of existing buildings in Egypt. This proposal helps in developing the system currently used in the assessment (GPRS) to be directed to existing buildings. These existing buildings are considered one of the most energy-consuming and waste-producing buildings, in addition to raising awareness among peoples or users   of these buildings to increase their contribution to preserving. The proposed system for evaluating existing buildings called the Green Pyramid System for Existing Buildings (GPRS for EB) is based on the criteria listed among The rating system (LEED EB O+M), after being modified to be more compatible with the local environment in Egypt. This brings the research to a proposed system for the green pyramid rating system for existing buildings